A bibliometric analysis of emerging adulthood in the context of higher education institutions: A psychological perspectives - Wider, Walton; Muhammad Ashraf, Fauzi; Gan, Su Wan; Yap, Chin Choo; Mohd Wafiy Akmal, Ahmad Khadri; Siti Sarah, Maidin (Elsevier Ltd, 2023)
In recent years, there has been a rise in studies aimed at better understanding the needs and traits of emerging adults and the role that higher education institutions play in their development and success. Despite the relevance of higher education institutions to the emerging adulthood development, there has been scant work done to synthesise the literature on this topic. A bibliometric method was utilised to retrieve 2484 journal articles from Web of Science (WoS). Utilizing co-citation analysis and co-word analysis, we determined the most influential publications, mapped the knowledge structure, and predicted future trends. The results of the co-citation analysis indicate five clusters, while the co-word analysis indicates four. The results could be used as a roadmap for the future of research on emerging adults by a variety of interested parties, including policymakers, university administrators, funders, and academics.